Pembuatan Media Pembelajaran Menggunakan Kodular untuk Tata Bahasa A2 (Jurnal Insan Pendidikan dan Sosial Humaniora, 2024)
Family well-being is very important for the lives of individuals and communities. A happy and The problem with learning German grammar at the A2 level is that many students still struggle to understand sentence structure, especially when using the perfect tense, subordinate clauses with "weil," and the genitive case. Students often find it challenging to remember grammar rules and how to apply them in sentences. The aim of this study is to develop interactive learning media in the form of Kodular-based applications to address these issues and support learning German grammar at the A2 level. The app is designed with relevant grammar materials and uses the 4D model development method (Define, Design, Develop, Disseminate), which reaches only the development stage without dissemination. The app was created on the visual platform Kodular, which enables users to develop Android apps without programming knowledge. The results show that the app is an effective learning medium, with a validation score of 90 (excellent) for the material content and 92.5 (excellent) for the media aspects. With a file size of 5.08 MB, this application enables users to learn German grammar independently anytime and anywhere.